Analysis Best Practice Policy Road Pricing to Overcome Negative Externalities of Motorized Vehicles in West Java - Danindya, Tiara Alyska; Putranti, Titi Muswati (Newinera Publisher, 2024)
This research analyzes best practice policy road pricing in overcoming the negative externalities caused by motorized vehicles in West Java. Negative externalities, such as traffic congestion and air pollution, are major challenges for urban areas in West Java. Through implementation policy studies on road pricing in Singapore and London, this research analyzes the effectiveness of these policies in reducing congestion and improving air quality. The research methods used include literature reviews, policy analysis, and in-depth interviews. The research results show that road pricing can be an effective tool in reducing congestion and air pollution, if there is collaboration with the transportation department, police, and raharja services, adequate technology, effective outreach, and integration with improved public transportation. This policy must be designed holistically by taking into account related opportunities and issues. The role of communication, transparency and an inclusive approach is very important in increasing public acceptance of this policy.